The epidemiology and trends in management of acute Achilles tendon ruptures in Ontario, Canada: a population-based study of 27 607 patients. Issue 1 (January 2017) - Sheth, U.; Wasserstein, D.; Jenkinson, R.; Moineddin, R.; Kreder, H.; Jaglal, S. B.
Abstract : Aims: The aims of this study were to establish the incidence of acute Achilles tendon rupture (AATR) in a North American population, to select demographic subgroups and to examine trends in the management of this injury in the province of Ontario, Canada. Patients and Methods: Patients ≥ 18 years of age who presented with an AATR to an emergency department in Ontario, Canada between 1 January 2003 and 31 December 2013 were identified using administrative databases. The overall and annual incidence density rate (IDR) of AATR were calculated for all demographic subgroups. The annual rate of surgical repair was also calculated and compared between demographic subgroups. Results: A total of 27 607 patients (median age, 44 years; interquartile range 26 to 62; 66.5% male) sustained an AATR. The annual IDR increased from 18.0 to 29.3 per 100 000 person-years between 2003 and 2013. The mean IDR was highest among men between the ages of 40 and 49 years (46.0/100 000 person-years). The annual rate of surgical repair dropped from 20.1 in 2003 to 9.2 per 100 AATRs in 2013. There was a noticeable decline after 2009. Conclusion: The incidence of AATR is increasing in Ontario, while the annual rate of surgical repair is decreasing. A sharp decline in the rate of surgical repair was noted after 2009. This coincided with the publication of several high-quality RCTs which showed similar outcomes for the 'functional' non-operative management and surgical repair. Cite this article: Bone Joint J 2017;99-B:78–86.